Sistem Pakar Untuk Mengidentifikasi Kerusakan Perangkat PABX Panasonic NS1000 Dengan A* Pathfinding - Siswanto Siswanto; Helmy Ligaputra; M. Anif; Windu Gata; Basuki Hari Prasetyo (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Someone can be said to have the ability to handle damage to the Panasonic NS1000 PABX device and perform a configuration of at least 3 years or already have a certificate of competence and training. The problem to be investigated is the number of experts there is only one and can only identify 5 damage per day and 1 day there are 25 damage. PABX Panasonic NS1000 has 30 rules and 130 data symptoms of damage as its knowledge base. This Expert System is designed to identify damage to PABX Panasonic NS1000 mobile application-based applications using the A * (A star) pathfinding algorithm and the forward chaining method with the PHP (Jquery Mobile) programming language and the database using MySQL, as an application program used by PT. Mediatama Anugrah Citra to facilitate the process of troubleshooting and effective problem solving on target. The features in this expert system include the identification of problems, the identification process, up to the achievement of the goal state and solutions effectively, quickly and precisely, the user as the user or admin has its own login and access rights in identifying, entry and editing. In the programming case testing process it can be seen that the application of the A * Pathfinding algorithm with the heuristic function has proven ineffectively implemented in the expert system and the results of the UAT testing process, the respondents agree (above 91.23%) that overall the expert system helps the expert and can deduce damage to PABX devices correctly.